Rigorously interpreted quotation analysis for evaluating causal loop diagrams in late‐stage conceptualization. (6th March 2022) - Tomoaia‐Cotisel, Andrada; Allen, Samuel D.; Kim, Hyunjung; Andersen, David; Chalabi, Zaid
Abstract: As a field, system dynamics has made more progress in developing formal model evaluation methods that use quantitative data than ones that use qualitative data. This article describes a formal method for evaluating a causal loop diagram (CLD) in late‐stage conceptualization – referred to as rigorously interpreted quotation analysis – and illustrates its application in a case study. The method uses a systematic and explicit interpretive process to confirm or disconfirm all diagram elements in a CLD by comparing it to stakeholders' verbatim descriptions of their experiences in a complex dynamic situation. In so doing, this method enables the resolution of discrepancies between a CLD and qualitative data, building confidence in the structural aspects of a dynamic hypothesis. It does so via a process that is approachable for experts and stakeholders alike. © 2022 System Dynamics Society.